PERBANDINGAN FLAT SLAB DENGAN PELAT KONVENSIONAL TERHADAP PENGARUH BEBAN LATERAL - Aldy Kurnia Saputra; Endah Kanti Pangestuti (DAS Institute, 2023)
Construction development in Indonesia continues to experience massive growth, especially in technology and innovation. In high-rise buildings, many structural developments have various forms of structural design. A new type of slab used in Indonesia has emerged in recent years: the flat slab. A flat slab is a reinforced concrete construction supported directly by columns without beams. By not using beams, it has the advantage of reducing floor height, faster implementation time, and more economical implementation costs. This research will redesign the structure of a 9-storey hospital building in Kudus with a flat slab structural system and then compare it with a conventional slab structural system using the ETABS and Spcoloumn programs. The earthquake load used refers to the PUSKIM website. This study compares both structural systems' structural period, inter-story deviation, and fundamental earthquake force. From the comparison between the flat slab structural system and the conventional plate, it was obtained that the value of the vibrating period of the flat slab structural system was 11.82% greater in the X direction and 12.82% in the Y direction than the conventional plate structural system. The inter-story deviation of the flat slab is 26.86% greater for the X direction and 28.87% for the Y direction than the conventional slab structural system. The mass (weight) of the flat slab structural system is 8.37% greater than that of the conventional slab structural system. The primary earthquake force of the flat slab is 8.36% greater for the X direction and 8.4% for the Y direction than the conventional slab structural system. So, it can be concluded that a flat slab is less efficient in resisting lateral loads than conventional slabs.